Systematic Review on the Effectiveness of Strategies for Increasing Insulin Bioavailability in Oral Route Delivery Systems Based on Manufacturing Techniques and Materials Used - KRISNA, ADIVA PUJA; Ningrum, Hendri Wahyu; Fimannuha, Tamara Laily; Puspita, Oktavia Eka (Journal of Drug Delivery and Therapeutics, 2021)
Diabetes is a metabolic disease characterized by hyperglycemia due to impaired insulin secretion, insulin action, or both. All patients with type 1 diabetes and many type 2 diabetes require insulin therapy to achieve reasonable glycemic control. During this time, insulin is given through the subcutaneous injection route because it can be destroyed by gastric acid when given orally. Until now, many studies have developed oral insulin therapy using various delivery system strategies. This systematic literature review aims to answer several questions about the effect of technique and material on increasing oral insulin bioavailability and the best technique and type of material that can produce the best oral insulin bioavailability. We searched for published articles regarding the development of oral route insulin. Bioavailability parameters were assessed based on plasma insulin levels for relative bioavailability values and/or plasma glucose levels for pharmacological bioavailability values. Conclusion: The manufacturing technique in the delivery system affects insulin stability in maintaining its conformation to provide a therapeutic effect. The type of substance affects insulin bioavailability through its properties in paving the way for insulin across various barriers in the digestive tract. To date, the best results in the development of oral insulin have obtained oral insulin bioavailability of 73.10% achieved by mesoporous silica nanoparticles (MSN) delivery system with layer-by-layer technique coated with [poly (methacrylic acid-co-vinyl triethoxylsilane)] (PMV)]. Keywords: bioavailability, diabetes, insulin, nanoparticles, oral delivery system.